Metal inhibition on the reactivity of manganese dioxide toward organic contaminant oxidation in relation to metal adsorption and ionic potential. (March 2017) - Jiang, Jing; Wang, Zhuopu; Chen, Yang; He, Anfei; Li, Jianliang; Sheng, G. Daniel
Abstract: Coexisting metal ions may significantly inhibit the oxidative reactivity of manganese oxides toward organic contaminants in metal-organic multi-pollutant waters. While the metal inhibition on the oxidation of organic contaminants by manganese oxides has previously been reported, the extent of the inhibition in relation to metal properties has not been established. Six alkali, alkaline, and transition metals, as well as two testing metals were evaluated for their abilities to inhibit the reactivity of birnessite. Regardless of the pathways of phenol and diuron oxidation (polymerization vs. breakdown), the extent of metal inhibition depended mainly on the metal itself and its concentration. The observed metal inhibition efficiency followed the order of Mn 2+  > Co 2+  > Cu 2+  > Al 3+  > Mg 2+  > K +, consistent with metal adsorption on birnessite. The first-order organic oxidation rate constant ( k obs ) was linearly negatively correlated with metal adsorption ( q e ) on birnessite. These observations demonstrated that the metal inhibition efficiency was determined by metal adsorption on birnessite. The slopes of the k obs - q e varied among metals and followed the order of K +  > Ca 2+  > Mg 2+  > Mn 2+  > Cd 2+  > Co 2+  > Cu 2+  > Al 3+ . These slopes defined intrinsic inhibitory abilities of metals. As metals were adsorbed hydrated on birnessite, the intrinsic inhibitory ability was significantly linearly correlated with ionic potentials of metals, leading to a single straight line. Metals with multiple d electrons in the outermost orbit with polarizing energy that promotes hydrolysis sat slightly below the line, and vice versa . Graphical abstract: Highlights: Dechlorination and hydroxylation are proposed in diuron oxidation by birnessite. Metal inhibition efficiencies are determined by metal adsorption on birnessite. Intrinsic metal inhibitory ability is correlated with ionic potentials of metals.